A retrospective cohort study describing characteristics of those repeatedly detained under Section 136 of the Mental Health Act over a 5-year period and the association with past abuse. (April 2022) - Adewusi, Laureen; Mark, Isabel; Wells, Paige; O'Brien, Aileen
Individuals repeatedly detained under Section 136 (S136) of the Mental Health Act account for a significant proportion of all detentions. This study provides a detailed analysis of those repeatedly detained ('repeat attenders') to a London Mental Health Trust, identifying key demographic profiles when compared to non-repeat attenders, describing core clinical characteristics and determining to what degree a past history of abuse might be associated with these. All detentions to the S136 suite at South West London and St George's Mental Health NHS Trust over a 5-year period (2015–2020) were examined. Data were collected retrospectively from electronic records. A total of 1767 patients had been detained, with 81 patients identified as being a 'repeat attenders' (having had > = 3 detentions to the S136 suite during the study period). Repeat attenders accounted for 400 detentions, 17.7% of all detentions. Repeat attenders included a higher proportion of females (49.4%, p = 0.0001), compared to non-repeat attenders, and a higher proportion of them were of white ethnicity (85.2%, p = 0.001). 52 (64%) patients reported being a victim of past abuse or trauma. Of repeat attenders who reported past abuse or trauma, a high proportion had diagnoses of personality disorders, with deliberate self-harm as the most common reason for detention. They were more commonly discharged home with community support, rather than considered for hospital admission. In light of these findings, this paper discusses support potential strategies for those most vulnerable to repeated S136 detention, thereby minimising the ever-growing number of S136 detentions in the UK.